SYNTHESIS AND STUDY OF RHENIUM(IV) DISULPHIDE - A. M. Ionov (Тонкие химические технологии, 2017)
Synthesis and study of complex chalcogenides in the low oxidation state opens unexpected new opportunities of studying some fundamental problems of condensed matter physics. Dichalcogenides of transition metals, i.e., compounds with the general formula MX2, where M is molybdenum, tungsten, rhenium etc., and X is sulphur, selenium or tellurium, are especially interesting. These dichalcogenides find applications in optoelectronic devices, radiophotonics, in laser physics, communication technology, etc. This study contains a survey of literature concerning the synthesis of sulphides of transition elements from different groups of the Periodic table in low oxidation states. A method of direct hightemperature synthesis of ReS2 from source components has been proposed and implemented. The synthesized compound was identified by the X-ray fluorescence, method of photoelectron spectroscopy and IR absorption spectroscopy. We show that rhenium(IV) disulphide crystallizes in CdI2 structural type. X-ray photoelectron spectroscopy shows that rhenium in the oxidation state of four is present. IR spectrum shows that rhenium(IV) disulphide structure in contrast to molybdenum(IV) disulphide is characterized by a greater deformation of the layers forming the crystal structure.